Urban Claims and the Right to the City Urban Claims and the Right to the City - Walker, Julian; Carvalho, Marcos Bau; Diaconescu, Ilinca (UCL Press, 2020)
Urban Claims and the Right to the City explores how contested processes of urban development, and the rights of city dwellers, are understood and interpreted from the perspective of women and men working, in different ways, at the grassroots in Salvador da Bahia, Brazil, and London, UK. In doing so, it represents the grounded voices of authors whose work and lives mean that they engage, on a daily basis, with issues related to housing and spatial rights, and identity struggles around race, gender, disability, sexuality, citizenship and class.